ARCHITECTURAL STYLE OR ALTERNATIVE PROTECTION AGAINST FULL-SCALE AGGRESSION - Kaliberda, Mykola (Theory and practice of design, 2025)
The article explores brutalism as an architectural style in both global and Ukrainian contexts, with a particular focus on its potential role as an alternative form of protection in times of large-scale military aggression. Purpose. The study aims to trace the historical origins and architectural features of brutalism, to analyze its sociocultural impact on urban environments, and to assess its potential adaptation in contemporary Ukraine as a symbol of resilience and security. Methodology. The research employs an interdisciplinary approach, combining historical-architectural analysis, typological studies, comparative analysis of Western and Ukrainian examples, as well as sociocultural and project-analytical methods. A systematic perspective made it possible to integrate aesthetic, cultural, and security-related aspects of brutalism. Results. The findings demonstrate that brutalism in Ukraine is not only a significant component of the architectural heritage of the second half of the 20th century but also a style that can be reinterpreted as an architectural strategy capable of providing both psychological reassurance and physical protection. Its massive structures, monolithic character, and minimalist design foster a sense of safety and may be adapted to contemporary urban and residential development. Scientific novelty. The article highlights the dual nature of brutalism: its architectural and cultural role in shaping urban identity, as well as its potential application in the field of security. For the first time, brutalism is proposed as a conceptual resource for creating “protected architecture” in conditions of war and crisis. Practical relevance. The research provides recommendations for integrating brutalist principles into the design of modern public and residential buildings that combine aesthetic and functional qualities with protective requirements. The results may be of value to architects, urban planners, and heritage specialists in developing resilient urban environments.